Pengaruh Stem Cell terhadap Akurasi Prediksi Diferensiasi Seluler Berbasis Artifical Intelligence dalam Bioteknologi - Aghisna Pertiwi; Putri Silvia Ariyanti; Dwi Haryani; Shintia Ratu Ismail; Indriyana Puspawati (PT Ilmu Data Indonesia, 2026)
This study aims to analyze the influence of stem cells on the accuracy of Artificial Intelligence-based cellular differentiation predictions in the field of biotechnology. The method used is a literature study with a qualitative-descriptive approach through the collection and analysis of various relevant scientific literature. The results of the study indicate that stem cells have a crucial role in the cellular differentiation process through complex biological mechanisms, thus producing high-value data for analysis. On the other hand, Artificial Intelligence can improve prediction accuracy by utilizing machine learning algorithms to process large and complex biological data. The integration between stem cells and Artificial Intelligence has made a significant contribution to the development of modern biotechnology, particularly in regenerative therapy and tissue engineering. However, there are still challenges in terms of data quality, the complexity of biological systems, and regulatory aspects that need to be considered. Thus, this study confirms that the collaboration between biological approaches and digital technology has great potential in improving the effectiveness and efficiency of cellular differentiation predictions in the future.